Defect Detection Procedure for Bridge - MAHYUDDIN, ABU BAKAR (Universiti malaysia sarawak (UNIMAS), 2002)
Under the title "Defect Detection Procedure for Bridge", which will clarify the defect justifications in conjunctions with bridge particularly from structures and other aspects of civil engineering. Thus research intension focusing on understanding the state or condition of defects event. The utmost information retrieval from this thesis is expected to be a convincing knowledge concerning the types ofdefects in bridge. Furthermore, techniques and materials employed towards bridge rehabilitation is briefly discussed. And lastly conclusion and recommendation were made regarding this thesis to repair any weakness exist.